Flexible Normal‐Tangential Force Sensor with Opposite Resistance Responding for Highly Sensitive Artificial Skin. (8th March 2018) - Mu, Chunhong; Song, Yuanqiang; Huang, Wutong; Ran, Ao; Sun, Rujie; Xie, Weihua; Zhang, Huaiwu
Abstract: An electronic skin (e‐skin) that can detect both normal and tangential forces with a differentiable signals output is essential for wearable electronics. A flexible, stretchable, and highly sensitive tactile sensor is presented that enables the detection of both normal and tangential forces, with specific opposite and thus easily being differentiated resistance changing outputs. The e‐skin, which is based on two‐sublayered carbon nanotubes (CNTs)/graphene oxide (GO) hybrid 3D conductive networks, that are anchored on a thin porous polydimethylsiloxane (PDMS) layer, is synthesized via a porogen (GO wrapped NaCl) assisted self‐assembling process. The fabricated CNTs/GO@PDMS‐based e‐skin shows superior sensitivity (gauge factor of 2.26 under a pressure loading of 1 kPa) to tangential force, moderate sensitivity (−0.31 kPa −1 at 0.05–3.8 kPa, and −0.03 kPa −1 at 3.8–6.3 kPa, respectively) to normal force, and a high‐reproducible response over 5000 loading cycles including stretching, bending, and shearing. For applications, the e‐skin can not only detect wrist pulsing, discriminating different roughness of surfaces, but also produce an obvious responding to an extremely slight ticking (<20 mg) from a feather, and even can real‐timely monitor human's breath and music in rhythm. Abstract : Wearable carbon nanotubes/graphene oxide@polydimethylsiloxane (CNTs/GO@PDMS)‐based e‐skin fabricated via a porogen‐assisted self‐assembling process produces specific opposite resistance changing outputs under normal and tangential forces, with superior sensitivity (gauge factor of 1.18) and robust durability. The e‐skin can produce an obvious response to an extremely light tickling (<20 mg) from a feather, and even can monitor human's breath and music in rhythm in real time.